Analisis Pengunaan Learning Management System Sebagai Media Pembelajaran Pada Mahasiswa Tahun Pertama - Aziz, Abdul; Widianto, Febri; Purwanto, Agung (Universitas Cokroaminoto Palopo, 2024)
Education is crucial in shaping a nation's future, especially in the era of globalization and information technology. Higher education, however, faces complexities such as unequal access and a lack of transparency, necessitating effective solutions. This research focuses on the pressing need for implementing a Learning Management System (LMS) to improve the efficiency and quality of learning. The research aims to identify factors influencing the effectiveness of LMS usage in higher education. It analyzes student participation, engagement levels in learning materials, and their impact on learning outcomes. The study contributes to understanding the dynamics of LMS usage, laying the groundwork for enhancements in the higher education environment. Qualitatively descriptive, the research centers on students at Darwan Ali University to provide a holistic overview of LMS adoption in higher education. Through purposive sampling, the main population includes students from Darwan Ali University, ensuring comprehensive representation. Data collection employs questionnaires and interviews. Questionnaires explore students' perceptions and experiences with LMS, while interviews provide in-depth insights. Confidentiality and data integrity are maintained during the distribution of questionnaires and interviews with students. Data analysis takes a qualitative, descriptive approach, identifying patterns, findings, and relationships among variables from questionnaires and interviews. Despite a preference for conventional methods, students at Darwan Ali University have integrated LMS into their learning, overcoming difficulties for an overall improvement in learning outcomes. The research highlights student acceptance of LMS, challenges faced, and positive impacts on learning outcomes. Privacy and data security concerns emphasize the need for attention to enhance user trust in online learning technology. Anticipated to contribute significantly, this research provides insights into LMS dynamics in higher education. It forms the basis for future improvements, aiming to create a more effective and secure online learning experience.